ASSESSMENT OF FENUGREEK SEED'S POTENTIAL IN MITIGATING LINAGLIPTIN-INDUCED PANCREATITIS: AN IN VIVO STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Many oral hypoglycemic drugs are available for the treatment of diabetes mellitus. Along with other hypoglycemics dipeptidylpeptidase-4 inhibitors i.e, linagliptin is one of the new drug which are used for the treatment of diabetes. The DPP4 inhibitors are gliptins that are used orally. The mechanism of DPP-4 inhibitors is to increase incretin levels (GLP-1 and GIP) which inhibit glucagon release, which in turn increases insulin secretion. Objectives: Linagliptin may cause pancreatitis and infections so the combination of Linagliptin and Fenugreek seeds can be helpful to reduce dose of Linagliptin and can increase its safety and efficacy..Methods: An in vivo study was conducted to evaluate the effects of linagliptin on diabetes. Blood samples from normal and diabetic male rats were analyzed and compared to a control diabetic group.Study Design: Experimental.Place and Duration: Study was conducted at University of Karachi, from November 2023 to April 2024.Results: The results showed that combination of linagliptin and Fenugreek seeds showed its potential in managing diabetes and has synergistic hypoglycemic activity. Linagliptin not only produced antidiabetic but it may produce severe pancreatitis and toxicity. Serum amylase and serum lipase  level  reduced with combination so it can increase protection against pancreatitis. Conclusion: The studied concluded that linagliptin have marked good antidiabetic activity and combination of linagliptin and Fenugreek seeds reduce the dose of linagliptin which in turn increase  its safety and efficacy and protecting the pancreas from damage and toxicity.